2018
DOI: 10.1159/000493717
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of MicroRNA-4463 Attenuates High-Glucose- and Hypoxia-Induced Endothelial Cell Injury by Targeting PNUTS

Abstract: Background/Aims: Vascular complications are the main reasons for disability and mortality associated with type 2 diabetes mellitus (T2DM) and numerous microRNAs (miRNAs) are involved in this process. Our previous study demonstrated that miR-4463 was increased in the plasma of T2DM patients combined with arteriosclerosis of low extremity artery (ASO). However, the role of miR-4463 remains unclear. Methods: miR-4463 expression in the vascular tissues of patients with ASO and T2DM and in human umbilical vein endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…The upregulation of miR-4463 expression enhanced H 2 O 2 -induced oxidative stress and promotes apoptosis in endothelial cells [ 52 ]. The inhibition of miR-4463 promoted human umbilical vein endothelial cell survival and reduced apoptosis under hypoxic conditions by targeting the protein phosphatase-1 nuclear targeting subunit [ 53 ]. In addition, miR-4463 promoted vascular smooth muscle cell migration, which is implicated in vascular diseases, by targeting angiomotin [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The upregulation of miR-4463 expression enhanced H 2 O 2 -induced oxidative stress and promotes apoptosis in endothelial cells [ 52 ]. The inhibition of miR-4463 promoted human umbilical vein endothelial cell survival and reduced apoptosis under hypoxic conditions by targeting the protein phosphatase-1 nuclear targeting subunit [ 53 ]. In addition, miR-4463 promoted vascular smooth muscle cell migration, which is implicated in vascular diseases, by targeting angiomotin [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…H 2 O 2 was added exogenously and shown to be the most convenient and effective method to construct oxidative stress models in different cells. H 2 O 2 is a ROS, which can enter the cell through the membrane and change the normal physiologic state of the cell (He et al, 2018). Studies have shown that ROS can induce apoptosis through the mitochondrial apoptotic pathway and activation of the NF‐κB and SAPK signalling pathways (Dhupal et al, 2018; Tanaka et al 2018; Yang et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs have also been associated with diabetic complications. For example, the expression of miR-4463 is elevated in T2DM patients with arteriosclerosis [96]. It was shown to attenuate cell apoptosis via peanut (PNUT)-mediated PTEN nuclear localization and the activation of the cell survival PI3K/AKT pathway in hypoxic and/or hyperglycemic endothelial cells.…”
Section: Diabetic Complicationsmentioning
confidence: 99%